Folklorystyka online w świetle problematyki dziedzictwa digitalnego - Krawczyk-Wasilewska, Violetta (Zeszyty Wiejskie, 2016)
In the digital age the notion of intangible cultural heritage has modern connotations that give the term new meanings and approaches. According to UNESCO and the EU authorities the “new” heritage needs to be safeguarded and protected as well as old resources inherited from generations. That is why a new folkloristics faces an interdisciplinary “digital turn”. The author presents the results of digitization process undertaken by major European folklore archives. But new archives need new materials (e.g. e-folklore vs. digital folklore) collected by new folklorists. The expansion of folklore field work towards digitally mediated environment and virtual reality is easy to be observed. Therefore, new methods of digital folklore collecting as well as new tools of research and documentation are challenges of the digital folkloristics.